Nonlinear Dielectric Nanoresonators and Metasurfaces: Toward Efficient Generation of Entangled Photons - Sharapova, Polina R.; Kruk, Sergey S.; Solntsev, Alexander S. (Laser & Photonics Reviews)
Keywords: Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Quantum-optical excitations of semiconductor nanostructures in a microcavity using a two-band model and a single-mode quantum field - Rose, Hendrik; Vasil'ev, A. N.; Tikhonova, O. V.; Meier, Torsten; Sharapova, Polina (Physical Review A)

Two-Colour Spectrally Multimode Integrated SU(1,1) Interferometer - Ferreri, Alessandro; Sharapova, Polina R. (Symmetry)
Multimode integrated interferometers have great potential for both spectral engineering and metrological applications. However, the material dispersion of integrated platforms constitutes an obstacle that limits the performance and precision of such interferometers. At the same time, two-colour nonlinear interferometers present an important tool for metrological applications, when measurements in a certain frequency range are difficult. In this manuscript, we theoretically developed and investigated an integrated multimode two-colour SU(1,1) interferometer operating in a supersensitive mode. By ensuring the proper design of the integrated platform, we suppressed the dispersion, thereby significantly increasing the visibility of the interference pattern. The use of a continuous wave pump laser provided the symmetry between the spectral shapes of the signal and idler photons concerning half the pump frequency, despite different photon colours. We demonstrate that such an interferometer overcomes the classical phase sensitivity limit for wide parametric gain ranges, when up to 3×104 photons are generated.
Keywords: Physics and Astronomy (miscellaneous); General Mathematics; Chemistry (miscellaneous); Computer Science (miscellaneous)

Steady states of Λ-type three-level systems excited by quantum light with various photon statistics in lossy cavities - Rose, Hendrik; Tikhonova, O V; Meier, Torsten; Sharapova, Polina (New Journal of Physics)
Abstract The interaction between quantum light and matter is being intensively studied for systems that are enclosed in high- Q cavities which strongly enhance the light–matter coupling. Cavities with low Q -factors are generally given less attention due to their high losses that quickly destroy quantum systems. However, bad cavities can be utilized for several applications, where lower Q -factors are required, e.g., to increase the spectral width of the cavity mode. In this work, we demonstrate that low- Q cavities can be beneficial for preparing specific electronic steady states when certain quantum states of light are applied. We investigate the interaction between quantum light with various statistics and matter represented by a Λ-type three-level system in lossy cavities, assuming that cavity losses are the dominant loss mechanism. We show that cavity losses lead to non-trivial electronic steady states that can be controlled by the loss rate and the initial statistics of the quantum fields. We discuss the mechanism of the formation of such steady states on the basis of the equations of motion and present both analytical expressions and numerical simulations for such steady states.
Keywords: General Physics and Astronomy

Theoretical analysis of correlations between two quantum fields exciting a three-level system using the cluster-expansion approach - Rose, Hendrik; Tikhonova, Olga V.; Meier, Torsten; Sharapova, Polina (Ultrafast Phenomena and Nanophotonics XXVI)